Transcending Taboos in Medical Ethics - Hans Thulesius (Grounded Theory Review: An International Journal)
The following is perhaps what Glaser would call a “theory bit” (1) from a write up of memos inspired by interview data leading up to a grounded theory of De-tabooing Dying Control (2).